Analysis of the influence on the hydraulic lifting circuit of the boom crane when the characteristics of the steel wire rope changes. Issue 1 (January 2021) - Fei, Y; Jiang, J; Sun, C
Abstract: In the process of lifting and landing of large hydraulic crane fully loaded, the working condition conversion makes the stress of steel wire rope change frequently and generate additional dynamic load, which makes the movement of the crane unstable and affects the working stability of the hydraulic system, and also leads to the fatigue damage of the tower structure and reduces the effective working life of the tower crane. In order to find the optimal dynamic characteristics of hydraulic system, the initial tension force, stiffness of hoisting wire rope and rigidity of variable amplitude wire rope of hoisting wire rope are studied respectively by means of machine-liquid integration simulation based on the AMESim, a kind of simulation software. The lifting mechanism of a type of closed hydraulic system is modelled and simulated. The results show that the maximum dynamic load of hoisting mechanism is reduced by 92.6% and the stabilization time is reduced by 49%. The optimized stiffness of hoisting wire rope reduces the dynamic load and peak pressure of hoisting mechanism by 5.2% and 4.3% respectively. The stiffness of the variable amplitude steel wire rope has little effect on the dynamic characteristics of lifting.